Determination of Premium Reserves for Whole Life Insurance Using the Canadian Method with Varying Premium Payment Periods - Wynnie, Illuminata; Yefan, Yefan (International Journal of Applied Sciences and Smart Technologies, 2025)
Premium reserves are essential funds prepared by insurance companies, particularly in life insurance, to cover potential future claims. These reserves are calculated based on premiums paid by policyholders and must be sufficient to meet all projected claim-related expenses. A lower reserve implies reduced financial liability and typically correlates with more affordable premium rates for policyholders. This study aims to analyze the determination of premium reserves using the Canadian and Prospective methods in traditional life insurance products, specifically whole life insurance, focusing on different premium payment periods. The Indonesian Population Mortality Table (TMPI) 2023 and the Bank Indonesia interest rate of 5.57% (as of April 2025) as the calculation basis. The results show that the Canadian method produces lower reserve values compared to the Prospective method and indicate a decreasing trend in reserve values as the premium payment period increases in both methods.